Bullying and depression: the moderating effect of social support, rejection and victimization profile - Palomares Ruiz, Ascensión; Oteiza-Nascimento, Arantxa; Toldos, Mª Paz; Serrano-Marugán, Isabel; Martín-Babarro, Javier (Anales de Psicología / Annals of Psychology, 2018)
Peer relationships can be shaped as influential factors in the prevalence of bullying episodes. This research aims to analyze the effect of school bullying on the levels of depression of the victims and to what extent it is affected by social support and status in the group and by the profile of victimization. Several hierarchical linear regression analyses were calculated, in a sample of 1063 students aged 10 to 14 (47.8% of girls, M = 11.59 years, SD = 1.21 years), from 10 school of the Region of Madrid. The degree of influence of the studied variables was observed: lack of social support, peer rejection, withdrawal and impulsivity behaviors, and the relationship of all of them with victimization and depression. Findings revealed the influence of the lack of social support on the depression of victimized students. However, peer rejection did not show influence on the levels of depression of the victims. In addition, victimization associated with internalizing characteristics showed a greater association with depression than victimization associated with an externalizing profile.